Nephroprotective effect of sugarcane (Saccharum officinarum L.) leaves ethanol extract on gentamicin-induced nephrotoxicity in rats - Ika Puspita Dewi; Merinda Aldiana; Zildjian Adela Viadina; Fifteen Aprila Fajrin; Diana Holidah; Fransiska Maria Christianty (Wolters Kluwer Medknow Publications, 2024)
Kidney damage is commonly attributed to using certain drugs, such as gentamicin, which causes elevated kidney parameters in blood and damage to renal tissue. This damage is often a result of oxidative stress, but it can be mitigated by using antioxidants. Several studies proved the potential of sugarcane (Saccharum officinarum L.) leaves as an antioxidant. Therefore, this experiment aimed to examine the nephroprotective action of sugarcane leaves. Twenty-five Wistar rats were separated into the normal, negative, and sugarcane leaf extract (SLE) (200, 400, and 600 mg/kg BW) groups. The animals were handled for 8 days, and then, the blood and tissue were collected 24 h later. The results revealed that SLE prevents increased creatinine, blood urea nitrogen, uric acid, and malondialdehyde levels. The histology analysis indicated that the extract improved kidney morphology and histopathology. Sugarcane leaves have the potential to be a nephroprotective agent.